Antioxidant efficiency in early life stages of the Antarctic silverfish Pleuragramma antarcticum: Responsiveness to pro-oxidant conditions of platelet ice and chemical exposure - REGOLI F.; BENEDETTI M.; FATTORINI D.; GORBI S.; NIGRO, MARCO (Aquatic Toxicology, 2005)
The Antarctic silverfish Pleuragramma antarcticum is a key organism in the ecology of Southern Ocean. Eggs with fully developed yolk-sac embryos and newly hatched larvae have been recently observed to occur in the platelet ice accumulating below the sea-ice layer. This environment has strong pro-oxidant characteristics at the beginning of austral spring, when the rapid growth of algal ice communities, the massive release of nutrients and the photoactivation of dissolved organic carbon and nitrates, all represent important sources for oxyradical formation. Such processes are concentrated in a short period of a few weeks which overlaps with the final development of P. antarcticum in platelet ice. The aim of this work was to characterize the antioxidant system in embryos of P. antarcticum and the responsiveness toward the natural increase of pro-oxidant conditions in early spring. Considering the lack of ecotoxicological data on this species and its pivotal importance in the ecosystem of Southern Ocean, the sensitivity of its early life stages was also evaluated after laboratory exposures to environmentally relevant doses of benzo(a)pyrene, as a model chemical potentially released from anthropogenic activities. Obtained results revealed a marked temporal increase of antioxidants in embryos of P. antarcticum as adaptive counteracting responses to oxidative conditions of platelet ice. Particularly prompt responses were observed for glutathione metabolism which, however, did not prevent formation of increasing levels of lipid peroxidation products; from the analysis of total oxyradical scavenging capacity (TOSC), the overall efficiency to neutralize peroxyl radicals remained almost constant while slightly lower TOSC values were obtained toward hydroxyl radicals at the end of sampling period. Laboratory exposures to 0.5-5 mu g/1 BaP caused a significant accumulation of this PAH but no significant effects on the activity of cytochrome P450. Antioxidants of exposed embryos showed less marked variations than embryos in ...